Az önkormányzati szolgáltatás-szervezés és szabályozás lehetőségei - Finta, István (Tér és Társadalom, 1998)
The classical service activities of the local governments are primarily the following: basic health care, social supply, education and public culture. The types of regulation are linked to the given economic activities, so in order to understand the service activities, it seems to be necessary to examine the given service from an economic aspect, too. 1. The organisational forms of the individual services Services, and in general any economic activity, can basically belong to three organisational forms: profit-oriented forms of organisation (economic companies, businesses) non-profit organisations (associations, foundations) budgetary institutions The German type of regulation orders specific tasks to the specific forms of organisation. According to this classification, there are budgetary organisations, own businesses or public companies. In the French practice, the legal framework (public service contracts), within which the given services are realised, are slightly more important compared to the forms of organisation. 2. Principles and solutions of organisation in the profit and the non-profit sector In the profit-oriented sector, there are theories such as the Total Quality Management or the Just in Time system. In the case of the latter, they do not produce for inventory, the products are transported to their destinations within a short time. Generally we can say that the principles of the market organisations are not adapted in the non-profit sector. 3. The role of public contract services in the organisation of services The public service contracts (whose synonym is "contracting out") is a tool of economic policy which aims at minimising the role of the state in the economic life. The existence and use in practice of such a tool is justified by the experience that the profit-oriented (and partly the non-profit) organisations are much more capable of an efficient management in an economic environment than the state organisations are.